Research Questions and Priorities for Tuberculosis: A Survey of Published Systematic Reviews and Meta-Analyses - Nicolau, Ioana (Public Library of Science, 2012)
BACKGROUND: Systematic reviews are increasingly informing policies in tuberculosis (TB) care and control. They may also be a source of questions for future research. As part of the process of developing the International Roadmap for TB Research, we did a systematic review of published systematic reviews on TB, to identify research priorities that are most frequently suggested in reviews. METHODOLOGY/PRINCIPAL FINDINGS: We searched EMBASE, MEDLINE, Web of Science, and the Cochrane Library for systematic reviews and meta-analyses on any aspect of TB published between 2005 and 2010. One reviewer extracted data and a second reviewer independently extracted data from a random subset of included studies. In total, 137 systematic reviews, with 141 research questions, were included in this review. We used the UK Health Research Classification System (HRCS) to help us classify the research questions and priorities. The three most common research topics were in the area of detection, screening and diagnosis of TB (32.6%), development and evaluation of treatments and therapeutic interventions (23.4%), and TB aetiology and risk factors (19.9%). The research priorities determined were mainly focused on the discovery and evaluation of bacteriological TB tests and drug-resistant TB tests and immunological tests. Other important topics of future research were genetic susceptibility linked to TB and disease determinants attributed to HIV/TB. Evaluation of drug treatments for TB, drug-resistant TB and HIV/TB were also frequently proposed research topics. CONCLUSIONS: Systematic reviews are a good source of key research priorities. Findings from our survey have informed the development of the International Roadmap for TB Research by the TB Research Movement.